Análise de aceitação de tecnologia no ambiente da Biblioteca Virtual Paul Otlet - Silva Segundo, Sanderli José da (2018)
Realizing the growing appeal for interactions based on Mixed Reality, this study begins by discussing the effects of the popularization of personal computers and the Internet in contemporary society. It presents Information Science from a technological perspective. It discusses how the concepts of ubiquity and pervasiveness carry out the transition from the product paradigm to the experience paradigm, within the scope of human-technology interaction. This dissertation brings a literary review of virtual reality, illustrating this technology with the Second Life platform. It presents the Paul Otlet Virtual Library, discussing the possibilities of the virtual environment as an alternative in the librarian work. It brings up the following question: what is the acceptance of participants of events promoted by virtual libraries in relation to their performance in non-immersive virtual reality platforms? In order to answer this, it develops a prospective analysis of virtual libraries using the technique and software developed by Michel Godet, taking as a temporal cut the performance of the Paul Otlet Virtual Library between 2012 and 2016. It presents, as a result, three probable future scenarios for Brazilian virtual libraries and demonstrates that their performance is directly linked to the library training offered by the national universities. The prospective method provided coherent results, explained the gaps found in two of the three problems collected by prospective members, the literary production and the cultural problem, from the perspective of the habit and ease of use of virtual reality technologies. The survey also indicated that the training of librarians is essential for the development of virtual libraries. Based on these results, this research had as general objective: to analyze the technological acceptance of participants of the Virtual Libraries Meeting, promoted by the Virtual Library Paul Otlet, about its performance in the non-immersive virtual environment of Second Life. To achieve this objective, a technological acceptance analysis was performed using the TAM 2 (Technology Acceptance Model) method, elaborated by Venkatesh and Davis (2000). The method was applied during the Virtual Libraries Meeting, promoted in 2017. The results indicated that the variables image, subjective norm and experience maintains a greater correlation with the "perceived utility" on the technology studied. That is, the research participants believe that knowing how to use virtual environments improves the professional image, expands the area of performance and highlights the user among his peers. It was observed that the increase or decrease of users and the emergence or stagnation of other virtual libraries will be consequences of the policies adopted in the formative phase.